I never promised you a rose garden - Greenberg, Joanne; Green, Hannah (The New American Library, 1964)
Chronicles the three-year battle of a mentally ill, but perceptive, teenage girl against a world of her own creation, emphasizing her relationship with the doctor who gave her the ammunition of self- understanding with which to destroy that world of fantasy.